Assessment of the impacts of oil prices on nigeria economy using COBB-douglas production function / Garba Mohammed Kabir and Sikiru Aliu Omotayo - Mohammed Kabir, Garba; Omotayo, Sikiru Aliu (Universiti Teknologi MARA, 2022)
Fluctuations in oil prices have been a global issue over the years. Although many studies have been carried out the majority of those studies relating to oil prices focused more on its effects on oil-consuming nations than oil-producing ones. This study, however, examines the vulnerability of the economy of the oil-producing country to oil price changes using Nigeria being an OPEC member as a case study. The Cobb-Douglas production function was used to formulate the appropriate model that relates oil prices with the economy of Nigeria. However, the close to close (standard deviation) volatility method was used to measure the amount of variability in oil prices. Nevertheless, the perpetual inventory method was used to estimate the accumulated physical capital of Nigeria and the problems of multicollinearity inherent in the data were attenuated using ridge regression techniques as capital cannot be left out while dealing with production.